2009
DOI: 10.1111/j.1365-2052.2008.01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Monophyletic origin of domestic bactrian camel (Camelus bactrianus) and its evolutionary relationship with the extant wild camel (Camelus bactrianus ferus)

Abstract: The evolutionary relationship between the domestic bactrian camel and the extant wild two-humped camel and the factual origin of the domestic bactrian camel remain elusive. We determined the sequence of mitochondrial cytb gene from 21 camel samples, including 18 domestic camels (three Camelus bactrianus xinjiang, three Camelus bactrianus sunite, three Camelus bactrianus alashan, three Camelus bactrianus red, three Camelus bactrianus brown and three Camelus bactrianus normal) and three wild camels (Camelus bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 22 publications
9
66
1
Order By: Relevance
“…For example, haplotypes H2, H5, H10-13, H15, and H16 were only found in Chinese domestic Bactrian camels; haplotypes H6, H7, and H8 were only found in Mongolian domestic Bactrian camels; but there were no specific haplotypes in Russian domestic Bactrian camels. In this study, all wild Bactrian camels consisted of only one haplotype (H14), in contrast to three haplotypes reported by a previous study (Ji et al, 2009b). Our results also suggest an extremely small effective population size of wild Bactrian camels, which are considered critically endangered by the International Union for Conservation of Nature.…”
Section: Haplotype Analysis Of Cytb Sequences From Domestic and Wild contrasting
confidence: 84%
See 3 more Smart Citations
“…For example, haplotypes H2, H5, H10-13, H15, and H16 were only found in Chinese domestic Bactrian camels; haplotypes H6, H7, and H8 were only found in Mongolian domestic Bactrian camels; but there were no specific haplotypes in Russian domestic Bactrian camels. In this study, all wild Bactrian camels consisted of only one haplotype (H14), in contrast to three haplotypes reported by a previous study (Ji et al, 2009b). Our results also suggest an extremely small effective population size of wild Bactrian camels, which are considered critically endangered by the International Union for Conservation of Nature.…”
Section: Haplotype Analysis Of Cytb Sequences From Domestic and Wild contrasting
confidence: 84%
“…Archaeological research suggests that Bactrian camels migrated from North America through the Bering Strait, and then arrived in Asia about 3 million years ago (Harrison, 1985). Later, during the Pleistocene Epoch (1.8 million to 10 000 years ago), Bactrian camel populations may have again been subdivided geographically, leading to a split of the two lineages (wild and domestic lineages) (Ji et al, 2009b). In this study, we found that 16 different haplotypes were divided into a domestic haplogroup and a wild haplogroup, and the phylogeographic analysis showed two major groups (wild and domestic Bactrian camel groups).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Despite their valuable use as draft animals, they are also used for milk, meat and fur production (Ji et al, 2009;Chuluunbat et al, 2014). In recent years, the number of Bactrian camels is getting smaller due to environmental changes and disease.…”
Section: Introductionmentioning
confidence: 99%